Anxiety, depression, and perceived wellbeing in antenatal women at risk of preterm birth: a retrospective cohort study - Worrall, Semra; Christiansen, Paul; Carlisle, Naomi; Fallon, Victoria; Khalil, Asma; Shennan, Andrew H.; Tribe, Rachel M.; Carter, Jenny; Silverio, Sergio A.; , The UK Preterm Clinical Network (Frontiers in Global Women's Health, 2024)
IntroductionWomen identified at risk for preterm may be vulnerable to developing mental health difficulties due to the increased likelihood of poor pregnancy outcome and uncertainty surrounding their delivery. Formal assessment of mental wellbeing in specialist preterm birth clinics is not routinely offered, but may offer the opportunity for early intervention.MethodsWe aimed to investigate if demographic characteristics and obstetric risk factors were associated with psychological wellbeing in women at risk of preterm birth. We explored associations between mental wellbeing and risk factors for preterm birth using hierarchical regression analyses.ResultsWhen demographic variables were considered alone, high body mass index (BMI) was significantly associated with anxiety (p = .026), however became non-significant when obstetric risk factors were also considered. Previous late miscarriage was associated with high anxiety (p = .049). Lower maternal age at estimated date of delivery (p = .019) and non-European ethnic heritage (p = .029) were significantly associated with depression. High maternal BMI (p < .001), being of any other non-European ethnic heritage (p = .043), currently smoking (p = .002), and previous spontaneous preterm birth (p = .017) were associated with lower perceived wellbeing.DiscussionThe results of this study highlight the importance of routinely monitoring mental health in women with relevant risk factors, particularly if they are already at risk of preterm birth.